Ethanol production by modified polyvinyl alcohol-immobilized Zymomonas mobilis and in situ membrane distillation under very high gravity condition. (15th September 2017) - Zhang, Quanguo; Nurhayati,; Cheng, Chieh-Lun; Lo, Yung-Chung; Nagarajan, Dillirani; Hu, Jianjun; Chang, Jo-Shu; Lee, Duu-Jong
Graphical abstract: Highlights: Very high gravity process is tested with immobilized Zymomonas mobilis cells. Vacuum membrane distillation in-situ removes fermented products. The integrated system yields higher yield and productivity of ethanol than literature. Abstract: Concentration of ethanol from the fermentation broth is an energy-intensive process. Very high gravity (VHG) process with modified polyvinyl alcohol-immobilized Zymomonas mobilis cells integrated with in situ bioethanol removal via vacuum membrane distillation (VMD) was proposed to mitigate product inhibition effects in VHG fermentation. The proposed VHG + VMD system, at 300 g/L glucose loading, produced 127.4 g/L (16.1% v/v) ethanol, at 63.7 g/L−h productivity and 84.9% glucose conversion rate, which is the highest in reported literature.